2016
DOI: 10.1073/pnas.1517903113
|View full text |Cite|
|
Sign up to set email alerts
|

Biotic homogenization can decrease landscape-scale forest multifunctionality

Abstract: Many experiments have shown that local biodiversity loss impairs the ability of ecosystems to maintain multiple ecosystem functions at high levels (multifunctionality). In contrast, the role of biodiversity in driving ecosystem multifunctionality at landscape scales remains unresolved. We used a comprehensive pan-European dataset, including 16 ecosystem functions measured in 209 forest plots across six European countries, and performed simulations to investigate how local plot-scale richness of tree species (α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(161 citation statements)
references
References 46 publications
8
151
0
2
Order By: Relevance
“…high betadiversity) can promote ecosystem multifunctionality at the landscape scale. This has turned out to be the case, as a high beta-diversity ensures that different localities complement each other in the ecosystem functions and services they provide (Mori et al 2016;van der Plas et al 2016b).…”
Section: Forest Biodiversity Multifunctionality and Trade-offs Amongmentioning
confidence: 99%
See 1 more Smart Citation
“…high betadiversity) can promote ecosystem multifunctionality at the landscape scale. This has turned out to be the case, as a high beta-diversity ensures that different localities complement each other in the ecosystem functions and services they provide (Mori et al 2016;van der Plas et al 2016b).…”
Section: Forest Biodiversity Multifunctionality and Trade-offs Amongmentioning
confidence: 99%
“…Pressures from human activities leading to forest loss, fragmentation and degradation (FAO 2015) have already caused much biodiversity decline and homogenization (Lindenmayer and Franklin 2002;Newbold et al 2015;van der Plas et al 2016b). These declines are expected to continue (e.g., Newbold et al 2015), especially in the rich forests of Central and South America, South and Southeast Asia and Africa, although the rate of forest loss has been slowing in recent years (Keenan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 shows a maximum with monocultures and an exponentially decreasing number of plots with increasing tree species numbers. The observation of decreasing productivity capacity with increasing mixtures is confirmed by a biodiversity experiment of Van der Plas et al (2016a) who compared European forest types and found the highest levels of ecosystem functions related to production for monocultures of Picea abies. Also results from long-term experimental plots similarly concluded to a higher maximum productivity in monocultures of Picea abies in deciduous temperate forests (Pretzsch, 2009).…”
Section: Forestsmentioning
confidence: 70%
“…P. halepensis is a conifer with two needles per brachyblast, while Q. ilex has a flat sclerophyllous leaf blade (Table 1). These leaf characteristics (i.e., flat and larger leaf size and needle for Q. ilex and P. halepnesis, respectively), with differences in the degree of sclerophylly, produce a leafy canopy type which, along with differences in the conducting system and branching architecture, would cause some differences in the water flow through the canopy between both species [25]. As regards the belowground structure, P. halepensis presents a moderate to shallow root system that determines the capacity to acquire water from soil (Table 1).…”
Section: Plant Functional Characteristics and Strategy To Cope With Dmentioning
confidence: 99%